METHODOLOGY FOR DETERMINING PROFITABILITY INDICATORS BY SEGMENTS IN TRADE ENTERPRISES - Bobomuradova Sarvinoz Ziyadullayevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article examines the methodological aspects of determining profitability indicators by segments in trade enterprises. In modern trade organizations, the diversification of products, sales channels, and territorial units creates the need to evaluate financial results separately for each segment. However, in many trade enterprises, income and expenses are recorded in aggregate form, which limits the possibility of accurately assessing the profitability of individual segments. The study proposes a methodological approach for determining profitability indicators by segments based on the allocation of revenues and expenses. The methodology includes the classification of trade segments by activity type, product group, and territorial unit, as well as the calculation of segment profitability, operating margin, cost ratio, and return on assets. The proposed approach makes it possible to identify the most profitable and least efficient segments, improve internal reporting, and support more effective managerial decision-making. The results of the study show that wholesale trade segments tend to generate higher profitability due to larger sales volumes and lower unit operating costs, while retail and regional branches often demonstrate lower profitability because of higher logistics and operating expenses. The proposed methodology can be applied by trade enterprises to improve segment reporting, optimize resource allocation, and enhance financial sustainability.